المرجعية الحقيقية للتنمية المستدامة بين المفهوم الوضعي والمفهوم الإسلامي، دلائل وحقائق - عثماني, أحسين (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES, 2014)
الملخص : تهدف هذه الدراسة إلى تقديم رؤية وصفية تحليلية عن التحولات التي تشهدها الدول والسعي نحو  حماية البيئة وتحقيق التنمية المستدامة، وكيف تتنافس اليوم على كسب رهان التقدم الحضاري، والادعاء بالسبق في الاشارة الى خطورة الوضع بتدهور البيئة وضرورة التدخل لتحقيق التنمية المستدامة.       وقد توصلت الدراسة إلى أن الاسلام هو الأقوم في هذا الميدان، فهو يحمل للانسانية  منظومة متكاملة في صناعة التنمية المستدامة به بدأت وعليه تكتمل، ما ترك مجالا من مجالات الحياة إلا وقد صبغها بصبغته ولا يحتاج الى غيره لاتمام تميزه.     Abstract:   This study aims to provide a vision and descriptive analytical transformations taking place in countries towards environmental protection and sustainable development, and how they compete to win a bet on the progress of civilization, and the prosecution take precedence in reference to the seriousness of the situation deteriorating environment and the need to intervene to achieve sustainable development.             The study found that Islam is the  excellence in this field, it carries an integrated system of humanity in the industry began its sustainable development and it is complete, leaving areas of life, however, has painted From all sides, did not leave the small thing  or large and does not require others to complete excellence.